Research on the high-temperature oxidation properties of high-Mn and low-Ni austenitic stainless steel containing an aluminizing layer - Yongjie Deng; Feipeng Qin; Yanjun Zhao; Jinyu Yu; Xiangxin Wei; Feng Wei (Journal of Materials Research and Technology)
High manganese (Mn) austenitic stainless steel substitutes expensive nickel (Ni) with more affordable Mn, thereby reducing production costs. However, its resistance to high-temperature oxidation is significantly compromised due to the formation of unstable Mn-rich oxides. To address this issue, this study investigates the application of an aluminizing layer on Fe–14Cr–10Mn-1.57Ni austenitic stainless steel to enhance its high-temperature oxidation resistance. The aluminized steel demonstrated a remarkable reduction in oxidation rate, with the surface oxidation rate constant being three orders of magnitude lower than that of the unaluminized stainless steel after exposure to 750 °C for 500 h. This improvement is attributed to the formation of a dense Al₂O₃ protective layer, which significantly enhances oxidation resistance. Furthermore, the study reveals a gradient in oxidation resistance between the aluminized surface and the core material, a phenomenon not previously reported in high-Mn, low-Ni steels. The primary oxidation mechanism is driven by the dense Al₂O₃ layer, which acts as a barrier, preventing the diffusion of oxygen to the steel substrate. These findings provide a cost-effective solution for enhancing the high-temperature durability of stainless steels, with potential applications in industries requiring materials with improved oxidation resistance, such as power plants and high-temperature furnaces.